Community participation in the education council, a view from the responsibility of the education manager (Revista Electrónica REDINE, 2018)
The following essay is an effort of theoretical reflection that aimed to highlight the role of the Educational Manager as the main manager of community participation in primary schools and to contrast some epistemological positions that, in relation to this subject, pose different Authors. Issues related to school management such as managerial leadership, conflict management and decision making were analyzed. Likewise, the importance of the mentioned aspects for the achievement of a democratic school management in accordance with the new educational policies was emphasized and the premises that are derived from the theoretical orientations as conclusion of each aspect are presented. This vision is not intended to be a finished document, but rather a call for attention on a topic in which a recent data item has been added, such as the Education Council.
Keywords: education manager; participation; school council